Pause : harnessing the life-changing power of giving yourself a break - O'Meara, Rachael (New York : TarcherPerigee, 2017)
"Feeling overwhelmed, burned out, or stuck? Discover the power of the pause. Sometimes life throws you for a loop. You're stressed out at your job; you're torn between work and family; your motivation and productivity are taking a nosedive. Your impulse might be to lean in and tough it out, but what you may really need to do is take a step back. Reassess your life with a clear head and dive back in with purpose and poise. In this enlightening book, Rachael O'Meara guides you through the steps of your own pause journey: - The signs that you're in need of a meaningful break - Planning your optimal pause--whether it's as short as a day or as long as an epic journey - Reentering the world with renewed clarity and purpose. Incorporating the latest findings from psychology and neuroscience and peppered with inspiring stories of successful pauses, this book will show you that the fastest way to happiness is to slow down. Whether you pause by taking a five-minute walk outside, spending a day unplugged from digital devices, or taking a few weeks off to yourself, Pause will give you the tools to find what "lights you up" and the ability to lead the most satisfying and fulfilling life you choose"--
Training for peak performance -- Five signs you need a pause -- Taking the pause plunge -- The art of mental flossing -- The pause dashboard: money, time, and activity -- The daily pause -- The digital device pause -- The extended pause -- Creating your pause playground -- Tips for a meaningful pause -- Reentry postpause -- Pausing as a way of life.
Includes bibliographical references and index.
Keywords: Burn out (Psychology) -- Prevention; Self-realization.; Stress management; Change